Histological Variations of the Glenoid Labrum in Dogs. (26th February 2013) - Sager, M.; Herten, M.; Dreiner, L.; Engelhardt, E.; Assheuer, J.; Kramer, M.; Jäger, M.
Summary: As the structure and clinical meaning of the canine glenoid labrum are repeatedly disputed up to now, an anatomical histological description of the structure and its varieties in older dogs is carried out. In this study, 20 shoulder joints are histologically and immunohistologically examined. The glenoid labrum (GL) is composed of up to three different zones: a transition zone composed of fibre cartilage with collagen fibres arranged like a fishnet‐like pattern, a zone of circularly leading fibre bundles and a meniscoid fold with synovial coverage. A variable recess exists between the GL and the joint surface.